Spasmolytic effect of citral and extracts of cymbopogon citratus on isolated rabbit ileum - Devi, Ramachandran Chitra; Sim, Si Mui; Ismail, Rosnah (2011)
Cymbopogon citratus, commonly known as lemongrass, has been shown to have antioxidant, antimicrobial and chemo-protective properties. Citral, a monoterpenoid, is the major constituent of C. citratus that gives off a lemony scent and is postulated to be responsible for most of its actions. In addition, C. citratus has been traditionally used to treat gastrointestinal discomforts, however, the scientific evidence for this is still lacking. Thus, the aim of the present study was to investigate the effect of the extracts of various parts of C. citratus (leaves, stems and roots) and citral on the visceral smooth muscle activity of rabbit ileum. The effect of the test substances were tested on the spontaneous contraction, acetylcholine (ACh)- and KCl-induced contractions. Citral at doses between 0.061 mM to 15.6 mM and the extract of leaves at doses between 0.001 mg/mL to 1 mg/mL significantly reduced the spontaneous, ACh- and KCl-induced ileal contractions. When the ileum was incubated in K+-rich-Ca2+-free Tyrodeâs solution, it showed only minute contractions. However, the strength of contraction was increased with the addition of increasing concentrations of CaCl2. The presence of citral almost abolished the effect of adding CaCl2, while the leaf extract shifted the calcium concentration-response curve to the right, suggesting a calcium antagonistic effect. These results were similar to that elicited by verapamil, a known calcium channel blocker. In addition, the spasmolytic effect of citral was observed to be reduced by the nitric oxide synthase inhibitor, L-NAME. In conclusion, citral and the leaf extract of C. citratus exhibited spasmolytic activity and it appeared that they may act as calcium antagonists. Furthermore, the relaxant effect of citral, but not that of the leaf extract may be mediated by nitric oxide suggesting the presence of other chemical components in the leaf extract other than citral.